The Correlation Between Fall Prevention Knowledge and Behavior in Stroke Outpatients. Issue 2 (April 2020) - Huang, Yanxia; Wu, Chanchan; Peng, Huiping; Chen, Qiaogen; Fan, Xiujun; Xiao, Lilan; Song, Baiyan; Wan, Lihong
Abstract : ABSTRACT: BACKGROUND: Stroke outpatients have a high risk of falling. However, fall prevention measures in the community are insufficient to effectively reduce the fall rate among outpatients with stroke. We aimed to determine the correlation between fall prevention knowledge and behavior among outpatients with stroke and provide new strategies for community fall prevention. METHODS: We recruited 124 patients with stroke who were followed up in the outpatient department of a tertiary hospital in Zhuhai, China. Patients were assessed using a general information questionnaire, a fall prevention knowledge questionnaire for patients with stroke, and the Stroke Fall Prevention Behavior Scale. IBM SPSS 22.0 software was used for statistical analysis. RESULTS: The median fall prevention knowledge was 82.76 (68.97, 93.10) points, out of 100. The mean (SD) score for fall prevention behavior was 2.90 (0.52; range, 1–4) points. Fall prevention knowledge scores were positively related to those fall prevention behavior (Spearman r = 0.454, P < .01). CONCLUSION: Levels of fall prevention knowledge among outpatients with stroke were adequate, and this population had medium to high levels of fall prevention behavior. Better knowledge was accompanied with better prevention of falls. However, whether enriching the knowledge could lead to improvement of fall prevention is still undetermined. Abstract : Supplemental digital content is available in the text.